How to: Surveillance of Clostridium difficile infections. (May 2018) - ,; Allerberger, F.; Delmée, M.; Van Broeck, J.; Vatcheva-Dobrevska, R.; Dobreva, E.; Matica, B.; Pieridou, D.; Krůtová, M.; Nyč, O.; Olesen, B.; Märtin, P.; et al.
Abstract: Background: The increasing incidence of Clostridium difficile infections (CDI) in healthcare settings in Europe since 2003 has affected both patients and healthcare systems. The implementation of effective CDI surveillance is key to enable monitoring of the occurrence and spread of C. difficile in healthcare and the timely detection of outbreaks. Aims: The aim of this review is to provide a summary of key components of effective CDI surveillance and to provide some practical recommendations. We also summarize the recent and current national CDI surveillance activities, to illustrate strengths and weaknesses of CDI surveillance in Europe. Sources: For the definition of key components of CDI surveillance, we consulted the current European Society of Clinical Microbiology and Infectious Diseases (ESCMID) CDI-related guidance documents and the European Centre for Disease Prevention and Control (ECDC) protocol for CDI surveillance in acute care hospitals. To summarize the recent and current national CDI surveillance activities, we discussed international multicentre CDI surveillance studies performed in 2005–13. In 2017, we also performed a new survey of existing CDI surveillance systems in 33 European countries. Content: Key components for CDI surveillance are appropriate case definitions of CDI, standardized CDI diagnostics, agreement on CDI case origin definition, and the presentation of CDI rates with well-defined numerators and denominators. Incorporation of microbiological data is required to provide information on prevailing PCR ribotypes and antimicrobial susceptibility to first-line CDI treatment drugs. In 2017, 20 European countries had a national CDI surveillance system and 21 countries participated in ECDC-coordinated CDI surveillance. Since 2014, the number of centres with capacity for C. difficile typing has increased to 35 reference or central laboratories in 26 European countries. Implications: Incidence rates of CDI, obtained from a standardized CDI surveillance system, can be used as an important quality indicator of healthcare at hospital as well as country level. Graphical abstract: